Penggunaan Deiksis Dalam Percakapan Antara Pelanggan Dan Pelaku Umkm Di Tanean Suramadu - Aisyah Aisyah (Journal of Social, Culture, and Language, 2024)
This research analyzes the use of deixis in conversations between customers and UMKM actors that occur in Tanean Suramadu Area, Sekarbungu, Labang Bangkalan. The researcher uses the theory of George Yule which explains about deixis and also the types of deixis. So, from the theory that has been presented, it can be concluded that this research will use a qualitative approach to classify and also conclude the main data from the data sources that have been obtained. The use of deixis in conversations in the business realm has an important role, more precisely between UMKM actors that occur in Tanean Suramadu. Here are some examples of the benefits of using deixis, including; 1). It can connect the speaker (either the seller or the buyer) with the situation or what is commonly called the context that occurs 2). Making it easier to understand the words spoken by sellers and buyers 3). Creating effective communication between customers and UMKM actors during the conversation. Based on the analysis, the researcher found 85 types of deixis which are divided into three types of deixis including: person deixis (first person, second person, and third person), place deixis (spatial), and also time deixis (temporal). The use of persona deixis is the most frequently used type of deixis in conversations between customers and UMKM actors in Tanean Suramadu area.